Hippocampal versus cortical deletion of cholinergic receptor muscarinic 1 in mice differentially affects post-translational modifications and supramolecular assembly of respiratory chain-associated proteins, mitochondrial ultrastructure, and respiration: implications in Alzheimer’s disease - Sabbir, Mohammad Golam; Swanson, Mamiko; Speth, Robert C.; Albensi, Benedict C. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: In a previous retrospective study using postmortem human brain tissues, we demonstrated that loss of Cholinergic Receptor Muscarinic 1 (CHRM1) in the temporal cortex of a subset of Alzheimer's patients was associated with poor survival, whereas similar loss in the hippocampus showed no such association. Mitochondrial dysfunction underlies Alzheimer's pathogenesis. Therefore, to investigate the mechanistic basis of our findings, we evaluated cortical mitochondrial phenotypes in Chrm1 knockout (Chrm1-/-) mice. Cortical Chrm1 loss resulted in reduced respiration, reduced supramolecular assembly of respiratory protein complexes, and caused mitochondrial ultrastructural abnormalities. These mouse-based findings mechanistically linked cortical CHRM1 loss with poor survival of Alzheimer’s patients. However, evaluation of the effect of Chrm1 loss on mouse hippocampal mitochondrial characteristics is necessary to fully understand our retrospective human tissue-based observations. This is the objective of this study. Methods: Enriched hippocampal and cortical mitochondrial fractions (EHMFs/ECMFs, respectively) derived from wild-type and Chrm1-/- mice were used to measure respiration by quantifying real-time oxygen consumption, supramolecular assembly of oxidative phosphorylation (OXPHOS)-associated proteins by blue native polyacrylamide gel electrophoresis, post-translational modifications (PTMs) by isoelectric focusing (IEF), and mitochondrial ultrastructure by electron microscopy. Results: In contrast to our previous observations in Chrm1-/- ECMFs, EHMFs of Chrm1-/ mice significantly increased respiration with a concomitant increase in the supramolecular assembly of OXPHOS-associated proteins, specifically Atp5a and Uqcrc2, with no mitochondrial ultrastructural alterations. IEF of ECMFs and EHMFs from Chrm1-/- mice showed a decrease and an increase, respectively in a negatively charged (pH3) fraction of Atp5a relative to the wild-type mice, with a corresponding decrease or increase in the supramolecular assembly of Atp5a and respiration indicating a tissue-specific signaling effect. Discussion: Our findings indicate that loss of Chrm1 in the cortex causes structural, and physiological alterations to mitochondria that compromise neuronal function, whereas Chrm1 loss in the hippocampus may benefit neuronal function by enhancing mitochondrial function. This brain region-specific differential effect of Chrm1 deletion on mitochondrial function supports our human brain region-based findings and Chrm1-/- mouse behavioral phenotypes. Furthermore, our study indicates that Chrm1-mediated brain region-specific differential PTMs of Atp5a may alter complex-V supramolecular assembly which in turn regulates mitochondrial structure-function.